Binge drinking: a pattern associated with a risk of problems of alcohol use among university students - André Bedendo; André Luiz Monezi Andrade; Emérita Sátiro Opaleye; Ana Regina Noto (Universidade de São Paulo, 2017)
ABSTRACT Objective: to evaluate problems associated with alcohol use among university students who reported binge drinking in comparison to students who consumed alcohol without binging. Method: a cross-sectional study among university students (N=2,408) who accessed the website about alcohol use. Logistic and linear regression models were included in the statistical analyzes. Results: alcohol use in the last three months was reported by 89.2% of university students; 51.6% reported binge drinking. Compared to students who did not binge drink, university students who presented this pattern were more likely to report all evaluated problems, among them: black out (aOR: 5.4); having academic problems (aOR: 3.4); acting impulsively and having regrets (aOR: 2.9); getting involved in fights (aOR: 2.6); drinking and driving (aOR: 2.6) and accepting a ride with someone who had drunk alcohol (aOR: 1.8). Students who binged also had higher scores on the Alcohol Use Disorders Identification Test (b=4.6; p<0.001), more negative consequences (b=1.0; p<0.001) and a reduced perception of the negativity of the consequences (b=-0.5; p<0.01). Conclusion: binge drinking was associated with an increase in the chances of manifesting problems related to alcohol use. The conclusions of this study cannot be generalized for all of the Brazilian population.